Artificial Insemination, livestock productivity and economic growth in Senegal - Cabral, Joseph François (International Food Policy Research Institute, 2016)
This paper assesses the effects of an artificial insemination program implemented in Senegal’s cow sector from 2008 to 2011. The program aimed to boost cow production in order to increase the sector’s supply of raw milk, processed milk, processed meat, and leather. We first build a dynamic recursive general equilibrium model in which the total factor productivity (TFP) is endogenized and expressed as a function of i) R&D and externalities for the cross-bred cows and ii) only externalities for traditional cows. We then simulate the effects of the artificial insemination program on sectors and factors remuneration, and hence GDP and welfare. The results show that production of cross-bred and local cows significantly increases under the program, as does production of processed meat, raw milk, processed milk, and leather. However, the increase in TFP seems to have a depressive effect on returns to factors, as less intensive factors used by cow sector are needed to produce the same output. Therefore, income for all households tends to decrease. However, consumption prices also decrease for all households, and the price effects seem to overcome the income effects. Households from sylvo pastoral rural areas, from urban cities (Dakar and other cities), and from the groundnut belt see their welfare increase from this program, while households in Southern Senegal, Eastern Senegal, and the Senegal River and Niayes area see decreased welfare.